Method for enhancing interface bonding strength of insulating substrate and metal layer
By coating the modified silane coupling agent-graphene composite liquid on the insulating substrate, the problem of insufficient interface bonding strength between the insulating substrate and the metal layer is solved, and higher interface bonding strength and conductive properties are achieved.
Patent Information
- Application Number
- CN202411593551.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In the prior art, the interface bonding strength between the insulating substrate and the metal layer is insufficient, which affects the overall performance of the product.
By coating the modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate, the interface bond strength between the conductive layer and the metal layer and the conductive layer and the insulating substrate is enhanced by using the modified silane coupling agent and its hydrolysate.
The interface bonding strength between the insulating substrate and the metal layer is significantly improved, meeting actual use needs, and improving the density of the conductive layer and the conductive and mechanical properties of the overall structure.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electroplating, and in particular to a method for enhancing the bonding strength between an insulating substrate and a metal interface. Background Art
[0002] The traditional process of constructing a metal layer on an insulating substrate generally involves first depositing copper foil on the surface of the insulating substrate as a conductive interface by chemical plating, and then thickening the copper layer by electroplating to achieve the preparation of the metal layer. Although chemical copper plating technology is relatively mature, it still has the following inherent defects: (1) The reducing agent used in chemical copper plating is mostly toxic formaldehyde, which will cause serious pollution to the environment; (2) The chelating agent in the plating solution is complicated to handle, and a special chelating process is required to reduce the impact on wastewater treatment, which brings great challenges to environmental protection work; (3) The interface bonding strength with the low surface energy substrate is insufficient, which may affect the overall performance of the product.
[0003] In order to overcome the above defects, researchers have innovatively proposed a direct electroplating process. This process provides the necessary conductive basis for electroplating by coating a layer of conductive material on the surface of an insulating substrate. 2 The two-dimensional carbon nanomaterial composed of hybrid orbitals and the structure is a hexagonal honeycomb lattice structure, which makes it have excellent electrical conductivity and mechanical strength, and provides an operating basis for the direct electroplating technology of graphene as a conductive layer. For example, the Chinese invention patent with publication number CN110351956A provides a method for direct electroplating of circuit boards based on graphene film formation. This method forms a conductive layer on the circuit board through a graphene film formation process, successfully replacing the traditional chemical copper deposition step, and realizing direct electroplating on an insulating substrate. In addition, the Chinese invention patent with publication number CN110158132A also proposes a method for electroplating an insulating material. This method also realizes direct electroplating on an insulating substrate by constructing a graphite nanosheet circuit on the surface of the insulating material. However, the above two methods still have the problem of weak bonding between the metal layer and the surface of the insulating material.
[0004] In order to improve the interfacial bonding strength between the insulating substrate and the metal layer, the prior art also adds a bonding aid of an oligomer (molecular weight of 400-4000) with a sulfonic acid group, a sulfonyl group or a carboxylic acid group to the conductive layer. The bonding aid enhances the covalent connection between the conductive layer and the electroplated metal during the electroplating process, and simultaneously generates mutual hydrogen bonding with the surface of the insulating substrate to enhance the interfacial bonding strength between the insulating substrate and the metal layer. However, due to the limited covalent connection between the conductive layer and the metal layer and the limited hydrogen bonding between the conductive layer and the groups on the surface of the insulating substrate, the interfacial bonding strength between the insulating substrate and the metal layer is limited, which still cannot meet the actual use requirements. Summary of the invention
[0005] The purpose of the present invention is to propose a method for enhancing the interface bonding strength between an insulating substrate and a metal layer, by coating a modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate, utilizing the modified silane coupling agent and its hydrolysis product in the modified silane coupling agent-graphene composite liquid to enhance the interface bonding strength between the conductive layer and the metal layer and between the conductive layer and the insulating substrate, thereby greatly improving the interface bonding strength between the insulating substrate and the metal layer, so as to overcome the shortcomings of the prior art.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] A method for enhancing the interface bonding strength between an insulating substrate and a metal layer comprises the following steps:
[0008] A. grafting a modifier onto a silane coupling agent to obtain a modified silane coupling agent; hydrolyzing the modified silane coupling agent to obtain a modified silane coupling agent hydrolyzate; wherein the modifier contains an unsaturated nitrogen or sulfur functional group;
[0009] B. mixing the modified silane coupling agent hydrolyzate with the graphene solution to obtain a modified silane coupling agent-graphene composite solution; the content of graphene in the modified silane coupling agent-graphene composite solution is 0.01 to 10% by mass percentage;
[0010] C. coating the modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate to obtain a silane coupling agent-graphene composite coating, and forming an insulating substrate with a conductive layer after drying; wherein the insulating substrate contains a functional group that can react with a hydroxyl group;
[0011] D. Electroplating the insulating substrate with the conductive layer to obtain an insulating substrate with a metal layer.
[0012] Furthermore, in step A, the modifier includes any one of imidazole, 2-methylimidazole, 2-phenylimidazole, benzimidazole, benzotriazole, lysine and thiourea.
[0013] Furthermore, in step A, the silane coupling agent includes any one of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-aminopropyl triethoxysilane, 3-isocyanate propyl triethoxysilane and aniline methyl trimethyl silane.
[0014] Furthermore, in step A, the specific method of the hydrolysis treatment is:
[0015] Mixing the first solvent and water uniformly to obtain a first mixed solution;
[0016] The first mixed solution is stirred, and during the stirring process, a modified silane coupling agent is added dropwise to obtain a second mixed solution;
[0017] The pH value of the second mixed solution is adjusted to 1.5 to 6, and then the second mixed solution after the pH value adjustment is stirred until it is completely transparent to obtain a modified silane coupling agent hydrolyzate;
[0018] The first solvent includes any one of isopropanol and ethanol.
[0019] Furthermore, in the hydrolysis treatment, the mixing ratio of the first solvent to water is (5-10):1, calculated by mass ratio.
[0020] Furthermore, in step B, the graphene solution is prepared by:
[0021] The graphite powder, surfactant and water are mixed uniformly, and the graphene is obtained after ball milling, ultrasonication, filtration, washing and drying;
[0022] The graphene and the second solvent are mixed evenly to obtain a graphene solution.
[0023] Furthermore, in step B, the mixing ratio of the modified silane coupling agent hydrolyzate and the graphene solution is 1:(1-100) in terms of mass ratio.
[0024] Furthermore, step C specifically includes:
[0025] C1. coating the modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate to obtain a silane coupling agent-graphene composite base layer;
[0026] C2. Repeat step C1 4 to 20 times to obtain a silane coupling agent-graphene composite coating, and form an insulating substrate with a conductive layer after drying.
[0027] Further, in step C2, the specific method of the drying treatment is: drying the upper surface of the silane coupling agent-graphene composite coating;
[0028] The drying includes any one of high-energy laser scanning and high-temperature airflow baking.
[0029] Furthermore, in step C, the insulating substrate is a glass substrate, and step C specifically comprises: coating the modified silane coupling agent-graphene composite liquid on the surface of the activated glass substrate to obtain a silane coupling agent-graphene composite coating, and forming a glass substrate with a conductive layer after drying.
[0030] The technical solution provided by the present invention may include the following beneficial effects:
[0031] 1. The modified silane coupling agent in the modified silane coupling agent-graphene composite liquid can form silanol (Si-OH) after hydrolysis, and silanol can react with the amino, carboxyl and hydroxyl groups on the surface of the insulating substrate to form a strong covalent bond, thereby increasing the interfacial bonding strength between the modified silane coupling agent in the conductive layer and the insulating substrate. In addition, the above covalent bond can also act as a bridge to promote the connection between the graphene in the conductive layer and the insulating substrate, thereby increasing the interfacial bonding strength between the graphene in the conductive layer and the insulating substrate. That is, the condensation reaction between the hydrolysis product of the modified silane coupling agent in the conductive layer and the groups on the surface of the insulating substrate can improve the interfacial bonding strength between the conductive layer and the insulating substrate.
[0032] 2. Since the modifier contains unsaturated nitrogen or sulfur functional groups, the modified silane coupling agent also contains unsaturated nitrogen or sulfur functional groups. The lone pair of electrons in the unsaturated nitrogen or sulfur functional groups can form a stable coordination bond (-N-Me bond or -S-Me bond, Me represents a metal atom) with the empty orbital of the metal atom in the metal layer, thereby increasing the interfacial bonding strength between the modified silane coupling agent in the conductive layer and the metal layer. In addition, the above-mentioned coordination bond also plays a bridging role, promoting the connection between the graphene in the conductive layer and the metal layer, thereby increasing the interfacial bonding strength between the graphene in the conductive layer and the metal layer. That is, the coordination effect between the unsaturated nitrogen or sulfur functional groups of the modified silane coupling agent in the conductive layer and the metal atoms in the metal layer can improve the interfacial bonding strength between the conductive layer and the metal layer. DETAILED DESCRIPTION
[0033] The present technical solution provides a method for enhancing the interface bonding strength between an insulating substrate and a metal layer, comprising the following steps:
[0034] A. grafting a modifier onto a silane coupling agent to obtain a modified silane coupling agent; hydrolyzing the modified silane coupling agent to obtain a modified silane coupling agent hydrolyzate; wherein the modifier contains an unsaturated nitrogen or sulfur functional group;
[0035] B. mixing the modified silane coupling agent hydrolyzate with the graphene solution to obtain a modified silane coupling agent-graphene composite solution; the content of graphene in the modified silane coupling agent-graphene composite solution is 0.01 to 10% by mass percentage;
[0036] C. coating the modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate to obtain a silane coupling agent-graphene composite coating, and forming an insulating substrate with a conductive layer after drying; wherein the insulating substrate contains a functional group that can react with a hydroxyl group;
[0037] D. Electroplating the insulating substrate with the conductive layer to obtain an insulating substrate with a metal layer.
[0038] In order to solve the technical problem of insufficient interface bonding strength between the insulating substrate and the metal layer in the prior art, the present technical solution proposes a method for enhancing the interface bonding strength between the insulating substrate and the metal layer, by coating a modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate, and utilizing the modified silane coupling agent and its hydrolysis product in the modified silane coupling agent-graphene composite liquid to enhance the interface bonding strength between the conductive layer and the metal layer and between the conductive layer and the insulating substrate, thereby greatly improving the interface bonding strength between the insulating substrate and the metal layer, thereby meeting actual practical needs.
[0039] Specifically, in order to improve the interfacial bonding strength between the insulating substrate and the metal layer in the prior art, a bonding aid having a sulfonic acid group, a sulfonyl group or a carboxyl group (molecular weight of 400 to 4000) is generally added to the conductive layer to enhance the interfacial bonding strength between the insulating substrate and the metal layer. However, the degree of improving the interfacial bonding strength between the insulating substrate and the metal layer by the above method is limited and it is difficult to meet the actual use requirements. Therefore, the present technical solution cannot improve the interfacial bonding strength based on this principle.
[0040] In order to improve the interfacial bonding strength of insulating substrate and metal layer, modified silane coupling agent hydrolyzate is utilized to mix with graphene solution to obtain modified silane coupling agent-graphene composite liquid in the technical scheme, and modified silane coupling agent-graphene composite liquid is coated on the surface of insulating substrate to obtain silane coupling agent-graphene composite coating, and an insulating substrate with conductive layer is formed after drying. Wherein, the modified silane coupling agent in modified silane coupling agent-graphene composite liquid can form silanol (Si-OH) after hydrolysis, and silanol can react with the groups such as amine, carboxyl and hydroxyl on the surface of insulating substrate to form a firm covalent bond, thereby increasing the interfacial bonding strength of the modified silane coupling agent in conductive layer and insulating substrate. In addition, the above-mentioned covalent bond can also play a bridging role, promoting the connection between the graphene in conductive layer and insulating substrate, thereby increasing the interfacial bonding strength of the graphene in conductive layer and insulating substrate. That is, the condensation reaction between the hydrolyzate of the modified silane coupling agent in the conductive layer and the groups on the surface of the insulating substrate can improve the interface bonding strength between the conductive layer and the insulating substrate.
[0041] In addition, since the modifier contains unsaturated nitrogen or sulfur functional groups, the modified silane coupling agent also contains unsaturated nitrogen or sulfur functional groups. The lone pair of electrons in the unsaturated nitrogen or sulfur functional groups can form a stable coordination bond (-N-Me bond or -S-Me bond, Me represents a metal atom) with the empty orbit of the metal atom in the metal layer, thereby increasing the interface bonding strength between the modified silane coupling agent in the conductive layer and the metal layer. In addition, the above-mentioned coordination bond also plays a bridging role, promoting the connection between the graphene in the conductive layer and the metal layer, thereby increasing the interface bonding strength between the graphene in the conductive layer and the metal layer. That is, the coordination effect of the unsaturated nitrogen or sulfur functional groups of the modified silane coupling agent in the conductive layer and the metal atoms in the metal layer can improve the interface bonding strength between the conductive layer and the metal layer.
[0042] Furthermore, the unsaturated nitrogen or sulfur functional groups in the modified silane coupling agent can further stabilize the interface between the conductive layer and the insulating substrate through physical adsorption, promote the connection between the graphene in the conductive layer and the insulating substrate, and thus improve the interface bonding strength between the conductive layer and the insulating substrate.
[0043] Therefore, in the technical solution, the interface bonding strength between the conductive layer and the insulating substrate is enhanced by using the modified silane coupling agent and its hydrolysis product, and the interface bonding strength between the conductive layer and the metal layer is enhanced by using the modified silane coupling agent, so that the interface bonding strength between the insulating substrate and the metal layer can be greatly improved. In addition, compared with using a bonding aid to improve the interface bonding strength, the covalent bond formed by the hydrolysis product of the modified silane coupling agent, the silanol, reacts with the amino group, carboxyl group and hydroxyl group on the surface of the insulating substrate to form a stronger bond, and the coordination bond formed by the lone pair of electrons in the modified silane coupling agent and the metal atoms in the metal layer has a higher strength, which is more conducive to improving the interface bonding strength between the insulating substrate and the metal layer.
[0044] Furthermore, due to the improved interface bonding strength between the insulating substrate and the metal layer, the designed thickness of the metal layer can be increased, and the increased thickness of the metal layer is conducive to reducing the resistance, so that the metal circuit formed by etching the metal layer in the subsequent use process has higher conductivity. In addition, thanks to the improved interface bonding strength between the conductive layer and the insulating substrate, and the improved interface bonding strength between the conductive layer and the insulating substrate, the graphene in the conductive layer can give full play to its excellent conductivity and mechanical strength, which is conducive to improving the conductive performance and mechanical properties of the overall structure.
[0045] Secondly, the prior art generally utilizes an immersion method to achieve the attachment of the conductive layer to the insulating substrate, but this method takes a long time and it is difficult to obtain a dense conductive layer.
[0046] In the technical solution, the modified silane coupling agent-graphene composite liquid is coated on the surface of the insulating substrate by a coating method instead of an immersion method, which can not only shorten the preparation time of the conductive layer, but also because the modified silane coupling agent-graphene composite liquid used in the coating method has a high content of graphene (because the thickness of the silane coupling agent-graphene composite coating obtained on the surface of the insulating substrate is nanometer-level, only a very small amount of graphene is needed to meet the above requirements, therefore, even if the content of graphene in the modified silane coupling agent-graphene composite liquid is 0.01%, its content is relatively high), so that the graphene in the modified silane coupling agent-graphene composite liquid after drying can be retained on the surface of the insulating substrate; in addition, the interface bonding strength between the graphene and the insulating substrate is high, and the above two effects are conducive to obtaining a denser and thicker conductive layer. Furthermore, since the concentration of graphene in the modified silane coupling agent-graphene composite liquid is relatively high (i.e., the solid content of the modified silane coupling agent-graphene composite liquid is relatively high), even if there are holes on the surface of the insulating substrate, the modified silane coupling agent-graphene composite liquid can penetrate into it, which is beneficial to improve the completion of the electroplated metal on the substrate surface and the conductive properties and mechanical properties of the overall structure.
[0047] It should be noted that the electroplating method in this technical solution is a conventional method in the prior art and will not be described in detail here. In addition, the focus of this technical solution is to enhance the interface bonding strength between the insulating substrate and the metal layer. Therefore, this technical solution does not describe the process of obtaining patterning by using conventional etching technology in the art before or after step D.
[0048] Preferably, the insulating substrate includes any one of a glass substrate, a polyamide substrate and a glass fiber epoxy resin substrate.
[0049] Preferably, in step C, the thickness of the conductive layer is 10 to 50 nm.
[0050] (1) Due to the excellent conductivity of graphene, the thickness of the conductive layer is 10 to 50 nm, which can also provide efficient electron transmission, ensuring that the conductive layer plays a good conductive role in electronic devices or circuits; (2) Although the high mechanical strength of graphene itself makes the conductive layer have high mechanical strength, a too thin conductive layer may be easily damaged, affecting its stability and reliability in long-term use. When the thickness of the conductive layer is 10 to 50 nm, the conductive layer can take into account both conductive performance and mechanical strength, ensuring its durability in various application scenarios; (3) When the thickness of the conductive layer is 10 to 50 nm, the conductive layer is more tightly bonded to the insulating substrate; (4) An overly thick conductive layer will increase material costs and production time. Therefore, based on the above reasons, the present technical solution limits the thickness of the conductive layer so as to maximize cost-effectiveness while ensuring performance.
[0051] Further, in step A, the modifier includes any one of imidazole, 2-methylimidazole, 2-phenylimidazole, benzimidazole, benzotriazole, lysine and thiourea.
[0052] The technical solution optimizes the type of the modifier, which is beneficial to ensuring the performance of the modified silane coupling agent on the one hand, and is also beneficial to selecting raw materials according to actual needs and improving the flexibility of the method on the other hand.
[0053] Further, in step A, the silane coupling agent includes any one of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-aminopropyl triethoxysilane, 3-isocyanate propyl triethoxysilane and aniline methyl trimethyl silane.
[0054] Vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-aminopropyl triethoxysilane, 3-isocyanate propyl triethoxysilane and aniline methyl trimethylsilane can all be hydrolyzed to produce silanols, which is beneficial to ensure the performance of the modified silane coupling agent on the one hand, and on the other hand, it is also beneficial to select raw materials according to actual needs and improve the flexibility of the method.
[0055] Preferably, the silane coupling agent includes any one of vinyltriethoxysilane, vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane.
[0056] Vinyl triethoxysilane, vinyl trimethoxysilane and vinyl tri(β-methoxyethoxy)silane all have short carbon chains, small steric hindrance and relatively good hydrophilicity, which are conducive to improving the hydrolysis reaction rate of the modified silane coupling agent, thereby facilitating improving the interfacial bonding strength between the insulating substrate and the metal layer. In addition, the above-mentioned silane coupling agent has good stability, a simple preparation method, easy raw material acquisition, and low production cost, which is conducive to reducing production costs.
[0057] Further description, in step A, the specific method of the hydrolysis treatment is:
[0058] Mixing the first solvent and water uniformly to obtain a first mixed solution;
[0059] The first mixed solution is stirred, and during the stirring process, a modified silane coupling agent is added dropwise to obtain a second mixed solution;
[0060] The pH value of the second mixed solution is adjusted to 1.5 to 6, and then the second mixed solution after the pH value adjustment is stirred until it is completely transparent to obtain a modified silane coupling agent hydrolyzate;
[0061] The first solvent includes any one of isopropanol and ethanol.
[0062] Because the silanol generated by the hydrolysis of the modified silane coupling agent will also undergo a condensation reaction. That is, the hydrolysis process of the modified silane coupling agent simultaneously has two reactions, hydrolysis and condensation, and the above two reactions are in a competitive state. In order to ensure that the content of silanol in the system is as large as possible, the condensation reaction should be controlled. Since water can promote the hydrolysis reaction of the modified silane coupling agent, and isopropanol and ethanol can reduce the condensation reaction of silanol. Therefore, the technical solution adopts any one of isopropanol and ethanol to mix evenly with water to obtain a first mixed solution, so as to maximize the generation of silanol.
[0063] In addition, when the pH value of the second mixed solution is adjusted to 1.5-6, the difference between the hydrolysis reaction rate and the condensation reaction rate is large, which further increases the amount of silanol in the system, thereby facilitating the improvement of the interface bonding strength between the conductive layer and the insulating substrate.
[0064] It should be noted that when the modified silane coupling agent is not completely hydrolyzed, the second mixed solution after the pH value is adjusted is turbid; when the modified silane coupling agent is completely hydrolyzed, the second mixed solution after the pH value is adjusted is completely transparent. Therefore, in order to ensure that the modified silane coupling agent is completely hydrolyzed, the second mixed solution after the pH value is adjusted in the technical solution is stirred until it is completely transparent.
[0065] It is further explained that in the hydrolysis treatment, the mixing ratio of the first solvent to water is (5-10):1, calculated by mass ratio.
[0066] In the technical solution, the mixing ratio of the first solvent and water is limited, so that the hydrolysis rate of the hydrolysis process of the modified silane coupling agent reaches the maximum, the condensation reaction rate reaches the minimum, and the difference between the hydrolysis reaction rate and the condensation reaction rate is maximized, thereby further increasing the content of silanol in the hydrolyzate of the modified silane coupling agent and enhancing the interface bonding strength between the insulating substrate and the metal layer.
[0067] Further description, in step B, the preparation method of the graphene solution is:
[0068] The graphite powder, surfactant and water are mixed uniformly, and the graphene is obtained after ball milling, ultrasonication, filtration, washing and drying;
[0069] The graphene and the second solvent are mixed evenly to obtain a graphene solution.
[0070] The principle of obtaining graphene in step B is: graphite powder, surfactant and water are mixed, the surfactant is conducive to better dispersion of graphite powder in water and prevents agglomeration of graphite powder particles; ball milling is used to further refine graphite powder particles and increase their contact area with surfactant and water, which is conducive to subsequent dispersion and stripping; the mixture after ball milling is ultrasonically treated to further strip the graphite powder particles into thinner graphene. At the same time, ultrasonic treatment can also promote the adsorption of surfactant on the surface of graphite powder particles and enhance the dispersibility between graphenes; after ultrasonic treatment, the graphene is separated from the mixture by filtering operation; the filtered graphene is then washed and dried to remove the surfactant, water and other impurities remaining on the surface of the graphene to improve the purity of the graphene.
[0071] In addition, in addition to being beneficial to the dispersion of graphite powder and graphene, the long-chain alkyl groups in the molecular structure of surfactants can also be inserted into the interlayers of graphite in graphite powder, weakening the interlayer interaction force and promoting the exfoliation of graphite powder into graphene.
[0072] Preferably, the second solvent includes any one of ethanol, ethylene glycol, isopropanol, N-methylpyrrolidone and dichloromethane.
[0073] The surfactant includes any one of sodium dodecyl sulfonate, sodium tetrapropylene benzene sulfonate, sodium diisooctyl sulfosuccinate, sodium dibutyl naphthalene sulfonate, sodium dodecyl sulfate and polyethylene glycol octyl phenyl ether.
[0074] Further, in step B, the mixing ratio of the modified silane coupling agent hydrolyzate and the graphene solution is 1:(1-100) in terms of mass ratio.
[0075] In the present technical solution, by limiting the mixing ratio of the modified silane coupling agent hydrolyzate and the graphene solution, the content of the modified silane coupling agent and its hydrolyzate is sufficient, thereby being sufficient to enhance and improve the interface bonding strength between the conductive layer and the metal layer and between the conductive layer and the insulating substrate, thereby facilitating ensuring the interface bonding strength between the insulating substrate and the metal layer.
[0076] To further illustrate, step C specifically includes:
[0077] C1. coating the modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate to obtain a silane coupling agent-graphene composite base layer;
[0078] C2. Repeat step C1 4 to 20 times to obtain a silane coupling agent-graphene composite coating, and form an insulating substrate with a conductive layer after drying.
[0079] The modified silane coupling agent and its hydrolyzate play a role in enhancing the bonding force between graphene and the insulating substrate, while graphene is used to form a conductive layer due to its excellent conductive properties. Through 4 to 20 coatings, it is beneficial to make the graphene evenly distributed in the conductive layer, thereby forming a stable conductive layer with good conductive properties on the surface of the insulating substrate.
[0080] Further, in step C2, the specific method of the drying treatment is: drying the upper surface of the silane coupling agent-graphene composite coating;
[0081] The drying includes any one of high-energy laser scanning and high-temperature airflow baking.
[0082] The drying method in the prior art mainly adopts placing the insulating substrate coated with the modified silane coupling agent-graphene composite liquid in a vacuum drying oven for drying. However, in the vacuum drying oven, due to the vacuum state, the volatilization rate of the solvent is subject to certain restrictions, resulting in a relatively low drying rate; in addition, in the vacuum drying oven, the volatilization of the solvent is random and has no specific directionality, which makes it easy for the solvent to cause stress concentration inside the coating or cause unevenness on the coating surface during the volatilization process; in addition, the vacuum drying oven is mainly used to remove the solvent in the coating to dry and solidify it. After drying, the coating may still have a certain porosity or loose structure, affecting the density of the coating.
[0083] Furthermore, the high-energy laser beam has a fast drying speed, and the precise control of the laser can ensure that the coating is evenly heated, avoiding damage to the coating caused by local overheating; the high-temperature airflow baking has a high drying efficiency, and the solvent volatilization path can be controlled by adjusting the speed and direction of the airflow, which is conducive to forming a uniform coating. Therefore, in order to improve the above defects, the technical solution limits the drying method to any one of high-energy laser scanning and high-temperature airflow baking. The above drying methods can significantly accelerate the volatilization rate of the solvent, thereby improving the drying efficiency.
[0084] In addition, the upper surface of the silane coupling agent-graphene composite coating is dried so that the solvent escapes from top to bottom. The above-mentioned directional volatilization method helps to form a more uniform coating structure, reduce porosity and loose structure, and improve the density and conductivity of the coating. Further, when the solvent escapes from the coating surface, the surface tension of the residual liquid will give the graphene in the coating a downward force, making it more closely attached to the surface of the insulating substrate. The above-mentioned effect not only enhances the interface bonding strength between the graphene and the insulating substrate, but also helps to improve the stability and durability of the entire coating.
[0085] Preferably, the scanning energy of the high-energy laser scanning is 1 to 10 KeV, and the scanning speed is 50,000 to 100,000 pts / s;
[0086] The temperature of the high-temperature airflow baking is 100-150° C., and the airflow speed is 1-1.5 m / s.
[0087] Further description, the insulating substrate is a glass substrate, and step C is specifically as follows:
[0088] The modified silane coupling agent-graphene composite liquid is coated on the surface of a glass substrate that has been activated to obtain a silane coupling agent-graphene composite coating, and after drying, a glass substrate with a conductive layer is formed.
[0089] The activation treatment can introduce more hydroxyl groups -OH on the surface of the glass substrate, which is convenient for condensation with silanol after hydrolysis of the silane coupling agent to produce chemical bonds; at the same time, the activation treatment of the surface of the glass substrate can also increase its surface roughness or form a micro-nano structure on its surface, which helps the modified silane coupling agent to form a more solid mechanical anchor on the surface of the glass substrate, further improving its adhesion and durability. Therefore, the technical solution activates the glass substrate, which is conducive to improving the performance of the product.
[0090] It should be noted that the activation treatment method can adopt the plasma cleaning, catalyst activation and high temperature activation methods in the prior art, which are not limited here.
[0091] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0092] Example 1
[0093] A. grafting imidazole onto vinyl triethoxysilane to obtain a modified silane coupling agent; uniformly mixing isopropanol and water at a mass ratio of 5:1 to obtain a first mixed solution; stirring the first mixed solution, and dropwise adding the modified silane coupling agent during the stirring process to obtain a second mixed solution; adjusting the pH value of the second mixed solution to 4, and then stirring the second mixed solution after the pH value adjustment until it is completely transparent to obtain a modified silane coupling agent hydrolyzate;
[0094] B. Graphite powder, sodium dodecyl sulfate and water are mixed evenly, and graphene is obtained after ball milling, ultrasonication, filtration, washing and drying; graphene is mixed evenly with ethanol to obtain a graphene solution; modified silane coupling agent hydrolyzate with a mass ratio of 1:60 is mixed with the graphene solution to obtain a modified silane coupling agent-graphene composite liquid with a graphene content of 5%;
[0095] C. coating the modified silane coupling agent-graphene composite liquid on the surface of the activated glass substrate to obtain a silane coupling agent-graphene composite base layer; repeatedly coating the modified silane coupling agent-graphene composite liquid on the surface of the activated glass substrate 10 times to obtain a silane coupling agent-graphene composite coating; drying the upper surface of the silane coupling agent-graphene composite coating by scanning with a high-energy laser having a scanning energy of 5Kev and a scanning speed of 50000pts / s to form a glass substrate having a conductive layer; wherein the thickness of the conductive layer is 20nm;
[0096] D. Electroplating copper on the insulating substrate with the conductive layer to obtain a glass substrate with a metal layer; wherein the electroplating current density is 3A / dm 2 , the electroplating time is 40min.
[0097] Example 2
[0098] A. Grafting benzimidazole onto γ-aminopropyltriethoxysilane to obtain a modified silane coupling agent; uniformly mixing ethanol and water in a mass ratio of 8:1 to obtain a first mixed solution; stirring the first mixed solution, and dropwise adding the modified silane coupling agent during the stirring process to obtain a second mixed solution; adjusting the pH value of the second mixed solution to 5, and then stirring the second mixed solution after the pH value adjustment until it is completely transparent to obtain a modified silane coupling agent hydrolyzate;
[0099] B. Graphite powder, sodium dodecyl sulfate and water are mixed evenly, and graphene is obtained after ball milling, ultrasonication, filtration, washing and drying; Graphene is mixed evenly with N-methylpyrrolidone to obtain a graphene solution; A modified silane coupling agent hydrolyzate with a mass ratio of 1:50 is mixed with the graphene solution to obtain a modified silane coupling agent-graphene composite liquid with a graphene content of 8%;
[0100] C. coating the modified silane coupling agent-graphene composite liquid on the surface of the glass fiber epoxy resin substrate to obtain a silane coupling agent-graphene composite base layer; repeatedly coating the modified silane coupling agent-graphene composite liquid on the surface of the glass fiber epoxy resin substrate 8 times to obtain a silane coupling agent-graphene composite coating; drying the upper surface of the silane coupling agent-graphene composite coating using a high-temperature nitrogen gas flow at a temperature of 120° C. and an airflow velocity of 1.2 m / s to form a glass fiber epoxy resin substrate with a conductive layer; wherein the thickness of the conductive layer is 30 nm;
[0101] D. Electroplating copper on the glass fiber epoxy resin substrate with a conductive layer to obtain a glass fiber epoxy resin substrate with a metal layer; wherein the electroplating current density is 2A / dm 2 , the electroplating time is 35min.
[0102] Example 3
[0103] A. grafting benzotriazole onto vinyl tri(β-methoxyethoxy)silane to obtain a modified silane coupling agent; uniformly mixing isopropanol and water at a mass ratio of 10:1 to obtain a first mixed solution; stirring the first mixed solution, and dropwise adding the modified silane coupling agent during the stirring process to obtain a second mixed solution; adjusting the pH value of the second mixed solution to 3.5, and then stirring the second mixed solution after the pH value adjustment until it is completely transparent to obtain a modified silane coupling agent hydrolyzate;
[0104] B. Graphite powder, sodium dodecyl sulfate and water are mixed uniformly, and graphene is obtained after ball milling, ultrasonication, filtration, washing and drying; Graphene is mixed uniformly with N-methylpyrrolidone to obtain a graphene solution; A modified silane coupling agent hydrolyzate with a mass ratio of 1:80 is mixed with the graphene solution to obtain a modified silane coupling agent-graphene composite liquid with a graphene content of 10%;
[0105] C. coating the modified silane coupling agent-graphene composite liquid on the surface of the glass substrate to obtain a silane coupling agent-graphene composite base layer; repeatedly coating the modified silane coupling agent-graphene composite liquid on the surface of the glass substrate 8 times to obtain a silane coupling agent-graphene composite coating; drying the upper surface of the silane coupling agent-graphene composite coating using a high-temperature nitrogen gas flow at a temperature of 150° C. and an airflow velocity of 1.1 m / s to form a glass substrate having a conductive layer; wherein the thickness of the conductive layer is 25 nm;
[0106] D. Electroplating copper on the glass substrate with the conductive layer to obtain a glass substrate with a metal layer; wherein the electroplating current density is 2.5A / dm 2 , the electroplating time is 30min.
[0107] Comparative Example 1
[0108] The method and raw materials of Comparative Example 1 are the same as those of Example 1, except that there is no step A and step B in Comparative Example 1.
[0109] Comparative Example 2
[0110] Comparative Example 2 uses poly 2-acrylamide-2-methylpropanesulfonic acid to replace the modified silane coupling agent, and the remaining raw materials are the same as those in Example 1, that is, Comparative Example 2 is:
[0111] A. Graphite powder, sodium dodecyl sulfate and water are mixed evenly, and graphene is obtained after ball milling, ultrasonication, filtration, washing and drying; Graphene is mixed evenly with ethanol to obtain a graphene solution with a graphene content of 2%; Poly (2-acrylamide-2-methylpropanesulfonic acid) (binding aid) with a mass ratio of 1:60 is mixed with the graphene solution to obtain a binding aid-graphene composite solution;
[0112] B. coating the bonding aid-graphene composite liquid on the surface of the activated glass substrate to obtain a bonding aid-graphene composite base layer; repeating the above steps 10 times to obtain a bonding aid-graphene composite coating; using a high-energy laser with a scanning energy of 5Kev and a scanning speed of 50000pts / s to scan the bonding aid-graphene composite coating to dry it, thereby forming a glass substrate with a conductive layer; wherein the thickness of the conductive layer is 20nm;
[0113] C. Electroplating copper on the insulating substrate with the conductive layer to obtain a glass substrate with a metal layer; wherein the electroplating current density is 3A / dm 2 , the electroplating time is 40min.
[0114] The surfaces of the insulating substrates with metal layers prepared in the examples and comparative examples were observed, and the peel strength between the insulating substrate and the metal layer was tested using a tensile testing machine. The test results are shown in the following table:
[0115] sample Surface condition Peel strength (N / cm) Example 1 Smooth and dense 308.12 Example 2 Smooth and dense 307.61 Example 3 Smooth and dense 304.25 Comparative Example 1 Rough 213.81 Comparative Example 2 Rough 262.44
[0116] From the performance test results in the above table, it can be seen that the peel strength of the insulating substrate and the metal layer in the embodiment of the present technical solution is significantly higher than that of the insulating substrate and the metal layer in the comparative example, and the peel strength between the insulating substrate and the metal layer is closely related to the interface bonding strength between the insulating substrate and the metal layer. When the peel strength between the insulating substrate and the metal layer is greater, the interface bonding strength between the insulating substrate and the metal layer is also greater, and vice versa. Therefore, the interface bonding strength between the insulating substrate and the metal layer in the present technical solution is higher than the case where the interface bonding strength between the insulating substrate and the metal layer is not improved by using a modified silane coupling agent in the conventional technology, and is also higher than the technical solution that uses a bonding aid to improve the interface bonding strength between the insulating substrate and the metal layer, but the effect is not good.
[0117] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for enhancing the interface bonding strength between an insulating substrate and a metal layer, characterized in that: The following steps are involved: A. grafting the modifier to the silane coupling agent to obtain a modified silane coupling agent; The modified silane coupling agent is subjected to hydrolysis treatment to obtain a modified silane coupling agent hydrolyzate; wherein the modified agent contains an unsaturated nitrogen or sulfur functional group; B. mixing the modified silane coupling agent hydrolyzate with the graphene solution to obtain a modified silane coupling agent-graphene composite solution; the content of graphene in the modified silane coupling agent-graphene composite solution is 0.01 to 10% by mass percentage; C. coating the modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate to obtain a silane coupling agent-graphene composite coating, and forming an insulating substrate with a conductive layer after drying; wherein the insulating substrate contains a functional group that can react with a hydroxyl group; D. Electroplating the insulating substrate with the conductive layer to obtain an insulating substrate with a metal layer.
2. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 1, characterized in that: In step A, the modifier includes any one of imidazole, 2-methylimidazole, 2-phenylimidazole, benzimidazole, benzotriazole, lysine and thiourea.
3. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 1, characterized in that: In step A, the silane coupling agent includes any one of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-aminopropyl triethoxysilane, 3-isocyanate propyl triethoxysilane and aniline methyl trimethyl silane.
4. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 1, characterized in that: In step A, the specific method of the hydrolysis treatment is: Mixing the first solvent and water uniformly to obtain a first mixed solution; The first mixed solution is stirred, and during the stirring process, a modified silane coupling agent is added dropwise to obtain a second mixed solution; The pH value of the second mixed solution is adjusted to 1.5 to 6, and then the second mixed solution after the pH value adjustment is stirred until it is completely transparent to obtain a modified silane coupling agent hydrolyzate; The first solvent includes any one of isopropanol and ethanol.
5. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 4, characterized in that: In the hydrolysis treatment, the mixing ratio of the first solvent to water is (5-10):1 calculated by mass ratio.
6. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 1, characterized in that: In step B, the preparation method of the graphene solution is: The graphite powder, surfactant and water are mixed uniformly, and the graphene is obtained after ball milling, ultrasonication, filtration, washing and drying; The graphene and the second solvent are mixed evenly to obtain a graphene solution.
7. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 6, characterized in that: In step B, the mixing ratio of the modified silane coupling agent hydrolyzate and the graphene solution is 1:(1-100) in terms of mass ratio.
8. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 1, characterized in that: Step C specifically includes: C1. coating the modified silane coupling agent-graphene composite liquid on the surface of the insulating substrate to obtain a silane coupling agent-graphene composite base layer; C2. Repeat step C1 4 to 20 times to obtain a silane coupling agent-graphene composite coating, and form an insulating substrate with a conductive layer after drying.
9. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 8, characterized in that: In step C2, the specific method of the drying treatment is: drying the upper surface of the silane coupling agent-graphene composite coating; The drying includes any one of high-energy laser scanning and high-temperature airflow baking.
10. The method for enhancing the interface bonding strength between an insulating substrate and a metal layer according to claim 1, wherein in step C, the insulating substrate is a glass substrate, and step C specifically comprises: The modified silane coupling agent-graphene composite liquid is coated on the surface of a glass substrate that has been activated to obtain a silane coupling agent-graphene composite coating, and after drying, a glass substrate with a conductive layer is formed.
Citation Information
Patent Citations
Electroplating method of insulation material
CN110158132A
Method for directly electroplating circuit board based on graphene film formation
CN110351956A
Photopolymerizable compositions for electroless plating methods
CN106062630A
Electric-heating anti-icing coating and preparation method thereof
CN106111499A
Preparation method of graphene modified polymer composite material
CN112852076A